Morphology and toxin study of puffer fish collected from Sabah and Sarawak waters - Monaliza, Mohd Din. (Universiti Malaysia Sarawak (UNIMAS), 2013)
In Malaysia, fatal food poisonings associated with the consumption of puffer fish have occured for decades, but the causative species or toxins have never been documented. To date, there has been little srudy on morphological and verification of toxin profiles on puffer fish especially on costal Sabah and Sarawak waters, Attempts was made to identify the morphology and verify the toxin profile in Tetraodontidae species of puffer fish commonly found in Sabah and Sarawak coastal waters.